2023
DOI: 10.1159/000529546
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Relapse of Type 2 Diabetes Mellitus after Laparoscopic Sleeve Gastrectomy in Japanese Subjects: A Subgroup Analysis of J-SMART Study

Abstract: Introduction: Laparoscopic sleeve gastrectomy (LSG) for morbidly obese patients often result in remission of type 2 diabetes (T2DM), but diabetes relapses in some of those patients. The frequency of T2DM relapse in Asians and the factors involved have not been adequately investigated. Methods: The J-SMART study was conducted on 322 Japanese subjects with body mass index (BMI) ≥ 32 kg/m2 who underwent LSG at 10 accredited centers in Japan between 2011 and 2014. Of these, 82 T2DM subjects with diabetes in comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Third, there was a lack of detailed information on bariatric surgery. Although the effectiveness of bariatric surgery for diabetic patients has been shown, the number of bariatric surgeries in Japan remains low 45,46 and the indication for bariatric surgery is BMI ≥35, which would apply to only 3.0% of our study participants. Therefore, patients with BMI <35 could achieve remission with non‐surgical treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Third, there was a lack of detailed information on bariatric surgery. Although the effectiveness of bariatric surgery for diabetic patients has been shown, the number of bariatric surgeries in Japan remains low 45,46 and the indication for bariatric surgery is BMI ≥35, which would apply to only 3.0% of our study participants. Therefore, patients with BMI <35 could achieve remission with non‐surgical treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Mean body weight, BMI, VFA, and HbA1c, which tended to increase at 12 months after LSG, decreased significantly after the patients were treated with once-weekly semaglutide for one year. Although metabolic surgery can achieve 30 % weight reduction and high remission rate of type 2 diabetes [ 22 ], studies have shown that some patients have relapse of type 2 diabetes due to postoperative weight recurrence [ 7 , [23] , [24] , [25] ], and some have poor metabolic improvement due to inadequate postoperative weight reduction [ 6 , 26 ]. The results of this study suggest that once-weekly semaglutide may be an effective treatment for weight recurrence and worsening diabetes after bariatric surgery, supporting the finding of a report [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A nationwide survey conducted by the retrospective study group “Japanese Survey of Morbid and Treatment-Resistant Obesity” (J-SMART) reported percent total weight loss (TWL) of 29.9 % and complete diabetes remission rate of 75.6 % at 2 years after LSG [ 6 ]. On the other hand, 26.8 % of subjects had recurrence of diabetes along with suboptimal weight reduction and excess weight recurrence within 5 years after LSG in the J-SMART study [ 7 ]. In several studies, 16–37 % of subjects showed significant weight recurrence in the long term [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the long-term, intrinsic β-cell function shows minimal improvement despite clinical diabetes remission post-MBS, with progressive diminished function over time [31] . Other mechanisms of improvement in diabetes control after MBS include increase in gut glucose utilization and intestinal gluconeogenesis, reduced gut glucose absorption, changes in adipose tissue, circulating bile acids and gut microbiota, among others [35] . Hence, rapid improvement and even normalization of blood glucoses can be observed immediately after MBS, with diabetes remission occurring as early as 3-6 months after surgery.…”
Section: Course Of Diabetes After Metabolic Surgery: Mechanisms and P...mentioning
confidence: 99%
“…The incidence of diabetes remission after sleeve gastrectomy (SG) and gastric bypass (GB) can range from 23% to 75% depending on the definitions used for diabetes remission, the type of surgical procedure, age and severity of T2D, amongst other factors [29,35] . Prediction models have been proposed to assess the likelihood of diabetes remission after bariatric surgery.…”
Section: Course Of Diabetes After Metabolic Surgery: Mechanisms and P...mentioning
confidence: 99%